2012
DOI: 10.1111/j.1469-8986.2012.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Pupil size varies with word listening and response selection difficulty in older adults with hearing loss

Abstract: Listening to speech in noise can be exhausting, especially for older adults with impaired hearing. Pupil dilation is thought to track the difficulty associated with listening to speech at various intelligibility levels for young and middle-aged adults. This study examined changes in the pupil response with acoustic and lexical manipulations of difficulty in older adults with hearing loss. Participants identified words at two signal-to-noise ratios (SNRs) among options that could include a similar-sounding lexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
195
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(216 citation statements)
references
References 88 publications
10
195
0
1
Order By: Relevance
“…Incongruence between visual and auditory information may thus be detectable in terms of cognitive load, as reflected by pupil dilation. Indeed, research suggests that pupil dilation can serve as an indicator of listening effort and difficulty of processing speech (Kuchinsky et al 2013, 2014). In the context of TV commercials, pupil dilation can thus serve as a signal of listening difficulty (Kuchinsky et al 2013, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Incongruence between visual and auditory information may thus be detectable in terms of cognitive load, as reflected by pupil dilation. Indeed, research suggests that pupil dilation can serve as an indicator of listening effort and difficulty of processing speech (Kuchinsky et al 2013, 2014). In the context of TV commercials, pupil dilation can thus serve as a signal of listening difficulty (Kuchinsky et al 2013, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, there have been various approaches using psychophysiological measures such as pupillometry (Engelhardt et al, 2010;Kuchinsky et al, 2013;Zekveld et al, 2013;Zekveld and Kramer, 2014;Zekveld et al, 2010;, eye movement tracking (Ben-David et al, 2011), galvanic skin response, electromyographic activity, heart rate variability (Mackersie and Cones, 2011;Mackersie et al, 2014), and electroencephalography (EEG) frequency bands (Obleser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…XXXX; Kuchinsky et al 2013;Piquado et al 2010;Zekveld & Kramer 2014;Zekveld et al 2010), heart rate, skin conductance, skin temperature, EMG activity (e.g., Mackersie & Cones 2011), heart rate variability (e.g., Mackersie & Calderon-Moultrie, this issue, pp. XXXX), fMRI activity (Wild et al 2012), ERPs (Obleser & Kotz 2011), and EEG alpha power (Obleser et al 2012) (see McGarrigle et al 2014, for a summary of listening effort studies using physiological measures published between 2008 and 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers interpreted the observed changes as evidence that the physiological measure indicates listening effort or resource allocation (e.g., Koelewijn et al 2012;Mackersie & Cones 2011;Obleser & Kotz 2011;Piquado et al 2010;Wild et al 2012). Other researchers suggested that this provides evidence for a physiological correlate of cognitive load or processing load (e.g., Kramer et al 2013;Kuchinsky et al 2013;Zekveld & Kramer 2014;Zekveld et al 2010). This paper aims at challenging the first interpretation by pointing out that research on effort mobilization has demonstrated that the difficulty-effort relationship depends on many factors (see Pichora- One of the first authors acknowledging that the relationship between task difficulty and effort is not proportional was Kukla (1972).…”
Section: Introductionmentioning
confidence: 99%